Russian perceptions of the Boer and British Armies: An introduction through Russian documents - Shubin, Gennady (Scientia militaria : South African journal of military studies, 2012)
On the eve of the outbreak of the Anglo-Boer War in South Africa, Colonel N.S. Yermolov, the Russian Military agent [attaché] in London reported on October1, 1899: "The War is inevitable ... The decision has been made to dispatch there from Britain the first army corps and at least 70 thousand [troops] ... The War is scheduled for half a year; many mounted infantry are under preparation; carts and mules being purchased in America. The general draft disposition is to defend the border of Natal, [and] offensive from Port- Elizabeth towards Bloemfontein and Pretoria."   For days later, on 5 October 1899 (all the dates are according to the "new", that is European calendar) he sent another coded message to General Sollogub, the Head of the Military Studies Committee (Voyenny Ucheny Komitet) of the General Staff: "The War has started. The Boers crossed the borders." The War Minister Kuropatkin wrote on it the following instruction: "Since Britain recognised the Transvaal as a warring side it is necessary to send our Military Agent to Boers without delay.'' Colonel Yermolov's message (or the date on it) was wrong: the war began only on II October. Two days earlier, however, on 9 October 1899 the Russian War Minister instructed the Chief of the General Staff to appoint immediately two officers of the General Staff to be present, one on each side, in the case of war in South Africa.